Allelopathic effect of aqueous leaf extract of Parthenium hysterophorus on germination and seedling growth of the Gossypium hirsutum - P, Gangasuresh; A, Ajithal Begam; A, Saranya; P, Senthil kumar; M, Rajkumarbharathi (Journal of Research in Biology, 2011)
Weeds are sometimes considered as unwanted plants. Some weeds reduce human efficiency through physical discomfort caused by allergies and poisoning. Weeds such as parthenium (Parthenium hysterophorus) and rag weed (Limbrosia species) causes etching, hay fever and other debilitating allergies, which contribute markedly to chronic human illness and suffering. Cotton seeds were treated with different concentrations of leaf exudates of parthenium hysterophorus and the biochemical constituents of treated cotton plants were analysed. The protein and phenol were found to increase in treated plants due to the release of protease inhibitors. In addition to this, increase in the activity of Nitrate reductase and peroxidase were observed followed by dthe ecreased activity of catalase. The plants with higher concentration of phenol showed resistance to pest and they were healthy compound to that of controlled plants. The treated plants also showed some morphological variations. Increase in height was noted in 80% treated plants and there were no growth and decrease in 100% treated. This inhibitory effect was due to high concentration of first noted in 80% treated plants. Thus 80% treatment was found to have optimal activity